Parachordoma of Soft Tissues of the Arm: A Very Rare Tumour - Vicente Estrems Díaz; Francesc Xavier Bertó Martí; Víctor Zarzuela Sánchez; Maria Isabel Cabanes Ferrer; Antonio Bru Pomer (Case Reports in Orthopedics)
Parachordoma is an infrequent neoplasm that bears some histologic resemblance to chordoma. It affects both sexes, occurs typically during the fourth decade of life, and tends to present as a slow-growing painless mass at the level of the soft tissues of the extremities. Diagnosis should be based on immunohistochemical and cytogenetic studies, as the findings of imaging techniques are often unspecific. Although it is considered a benign lesion, its behavior tends to be locally aggressive, with reports of a recurrence rate of up to 20% and of several cases of metastasis. Fewer than 60 cases have been published in the English-speaking literature. In this paper we present the case of a 32-year-old male with a two-year history of parachordoma in the right wrist.